2020
DOI: 10.1016/j.ophtha.2019.10.037
|View full text |Cite
|
Sign up to set email alerts
|

Can Structural Grading of Foveal Hypoplasia Predict Future Vision in Infantile Nystagmus?

Abstract: Purpose: To evaluate structural grading and quantitative segmentation of foveal hypoplasia using handheld OCT, versus preferential looking (PL), as predictors of future vision in preverbal children with infantile nystagmus.Design: Longitudinal cohort study.Participants: Forty-two patients with infantile nystagmus (19 with albinism, 17 with idiopathic infantile nystagmus, and 6 with achromatopsia) were examined.Methods: Spectral-domain handheld OCT was performed in preverbal children up to 36 months of age. Fov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
60
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(70 citation statements)
references
References 26 publications
7
60
0
3
Order By: Relevance
“…15,16,26 Recently, it has been suggested that structural grading of foveal hypoplasia may predict future vision in patients with infantile nystagmus (including ACHM). 44 In our cohort, BCVA was better by six ETDRS letters on average in patients without foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 46%
“…15,16,26 Recently, it has been suggested that structural grading of foveal hypoplasia may predict future vision in patients with infantile nystagmus (including ACHM). 44 In our cohort, BCVA was better by six ETDRS letters on average in patients without foveal hypoplasia.…”
Section: Discussionmentioning
confidence: 46%
“…Our recent prediction study included OCT data for preverbal infants and young children at first examination, then BCVA was recorded when the child was old enough to participate in gold standard LogMAR chart testing. 4 Moreover, in the study by Casas-Llera et al, we wonder whether cataracts could have influenced BCVA? Or perhaps the subcapsular cataracts were not in the visual axis?…”
Section: Dear Editormentioning
confidence: 99%
“…We would like to highlight that handheld OCT is possible in awake infants with nystagmus from birth in our experience, without sedation or dilation, such as in our latest study with infants as young as 28 days old. 4 We accept that a great number of eye departments do not have access to or experience in handheld OCT imaging, therefore it was reasonable for the authors to exclude children too young to cooperate with conventional OCT.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…26 OCT has been used to describe the normal development of the optic nerve 27 and fovea 27 28 in children. OCT has also been used in a wide range of conditions within paediatric ophthalmology, including retinopathy of prematurity, 29 retinoblastoma, 30 nystagmus, 31 albinism, 32 achromatopsia, 33 foveal hypoplasia, 34 optic nerve hypoplasia, 35 primary congenital glaucoma, 36 microcephaly 37 and others. Furthermore, OCT has been successfully used as a diagnostic tool in a variety of conditions associated with ICH, including idiopathic ICH, craniosynostosis and hydrocephalus.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%